Foot Exercise Prevents the Risk of Neuropathy on Type 2 Diabetes Mellitus Patients Literature Review - Widia, Chita; Hidayat, Riyan; Hidayat, Riyan (Journal Physical Education, Health and Recreation, 2020)
Diabetes mellitus is a disease in which the body cannot automatically control glucose in its blood, a complication that often occurs in the lower limbs called diabetic feet. This study aims to determine the risk of neuropathy in type 2 diabetes mellitus sufferers who perform diabetic foot exercises. The research method is the Literature Review type of Narrative Review. The population of articles used is articles that are on Google Scholar and Scopus. The number of samples was 7 articles whose research title was about the effect of diabetic foot exercise on the risk of neuropathy in type 2 diabetes mellitus sufferers in the last ten years of publication. The results showed that 7 research articles used diabetic foot exercises to reduce the risk of neuropathy in type 2 diabetes mellitus sufferers